2020
DOI: 10.1097/or9.0000000000000032
|View full text |Cite
|
Sign up to set email alerts
|

Single cases from multiple perspectives: a qualitative study comparing the experiences of patients, patients’ caregivers, surgeons, and nurses when bad news is delivered about cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Physicians may develop physiological stress responses and anxiety, particularly when they assess the conversation as ‘unsatisfactory’ (Shaw et al 2013 ; Friedrichsen and Milberg 2006 ). Especially for patients, as recipients of bad news, this moment is often highly emotional and overwhelming (Matthews et al 2020 ; Monden et al 2016 ). Retrospectively, patients and their families described the BBN situation as a ‘turning point’ or biographical caesura (Bumb et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Physicians may develop physiological stress responses and anxiety, particularly when they assess the conversation as ‘unsatisfactory’ (Shaw et al 2013 ; Friedrichsen and Milberg 2006 ). Especially for patients, as recipients of bad news, this moment is often highly emotional and overwhelming (Matthews et al 2020 ; Monden et al 2016 ). Retrospectively, patients and their families described the BBN situation as a ‘turning point’ or biographical caesura (Bumb et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ALS imagery of our participants highlights the need to enhance meaningful relationships within and outside the family, including the support of trusted and/or specialized people, such as doctors and psychologists. A need highlighted is communication, which has already been considered in the literature as a problematic dimension that requires special care [ 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Within this area, the theme of how to communicate the diagnosis of an illness with an unfortunate outcome to children has been particularly noteworthy.…”
Section: Discussionmentioning
confidence: 99%
“…(10) Since nurses have the largest workload and more contact with patients and family members, they are key players in the disclosure of bad news, and should establish an important bond at this moment. (30,31) Results of previous studies showed the creation of the nurse/patient bond is essential for a relationship of trust between them. (29,31) Therefore, even if it is not the nurses who communicate the bad news, their presence is fundamental to establish the necessary confidence to the patient and family, besides being the professionals who provide continuity of care to these subjects, and follows all consequences of the announced news.…”
Section: Englishmentioning
confidence: 99%
“…(8,11,25) Therefore, it is important to highlight that this communication must occur as a team, because even if it is the physician or the nurse who conveys bad news, there is a repercussion that reaches all other professionals who deal with the patient. (30) In communicating bad news in delivering comprehensive care, nurses are fundamental professionals who favor the establishment of a relationship of trust between the parties. This highlights the need to promote the development of communication skills of such professionals to ensure quality care.…”
Section: Englishmentioning
confidence: 99%